Strategies and Challenges in Conventional and Digital Film Distribution and Exhibition in Indonesia - Iswahyuningtyas, Cici Eka; Hidayat, Mochammad Fadjar (Jurnal Komunikasi, 2021)
Today, media distribution and consumption can occur anytime, anywhere, anything, both conventional and digital. The change in media consumption behavior has brought many challenges for the Indonesian film industry, particularly distribution and exhibition. Film distribution should not just rely on the domestic market and film exhibitions through cinemas. The number of Indonesian cinemas and screens is not ideal, still concentrated in big cities, has low moviegoers, is dominated by foreign films, and lacks support from the government. This study intended to identify challenges and strategies for conventional and digital distribution and exhibition. Answer to that question, this study was carried qualitatively by conducting a literature review through meta-analysis related to history, experiences, and situations in some countries. Research findings indicate film distribution and exhibition need to run simultaneously conventional and digital. Digital distribution is urgent for expanding market size and cinemas revenue. The conventional distribution needs to be maintained because the highest film revenue still comes from cinemas exhibitions. Therefore, filmmakers should begin to organize their distribution strategy and expand cooperation with digital film providers. The government needs to build distribution infrastructures such as global film festivals and distribution agencies, also create policies related to exhibition incentives and tax rebates, especially for films with small audiences. Distribusi dan konsumsi media dewasa ini dapat dilakukan kapanpun, dimanapun, apapun, baik secara konvensional maupun digital. Perubahan perilaku konsumsi media membawa banyak tantangan bagi industri film di Indonesia, khususnya terkait aspek distribusi dan eksibisi. Distribusi film tidak boleh hanya bergantung pada pasar domestik dan mengandalkan eksibisi film melalui bioskop. Hal ini karena jumlah bioskop dan layar yang tersedia di Indonesia belum ideal, masih terpusat di kota besar, memiliki sedikit penonton, berada dalam dominasi film asing dan kurang mendapatkan dukungan dari pemerintah. Kajian ini dimaksudkan untuk mengetahui tantangan dan strategi dalam distribusi dan eksibisi film secara konvensional dan digital. Untuk menjawab pertanyaan tersebut kajian ini dilakukan secara kualitatif dengan melakukan kajian pustaka melalui analisis meta terkait sejarah, pengalaman, situasi yang terjadi di beberapa negara. Temuan penelitian menunjukkan bahwa distribusi dan eksibisi film perlu dilakukan secara simultan. Distribusi digital penting untuk memperluas pasar dan meningkatkan pendapatan. Distribusi konvensional perlu dipertahankan karena pendapatan film terbesar masih berasal dari distribusi melalui jalur bioskop. Oleh karena itu, pembuat film harus mulai mengatur sendiri strategi distribusinya dan meningkatkan kerjasama dengan provider film digital. Pemerintah perlu membangun infrastruktur distribusi seperti festival film dan agensi distribusi di tingkat global, dan membuat kebijakan terkait pemberian insentif eksibisi dan potongan pajak, khususnya bagi film dengan sedikit penonton.